Melatonin: a natural guardian in cancer treatment - Cao, Yurou; Zhang, Hang; Chen, Xubin; Li, Conghui; Chen, Jingxin (Frontiers in Pharmacology, 2025)
Melatonin (MLT), a naturally occurring hormone produced by the pineal gland, exhibits significant anticancer effects. It has superior antioxidant, inhibit tumor cell proliferation, migration, angiogenesis-inhibiting, and tumor cell apoptosis-inducing functions. Mechanistically, melatonin inhibits tumor development through epigenetic regulation, metabolic reprogramming, immune micro-environment, and regulation of important signaling pathways (PI3K/AKT). In addition, MLT significantly enhances anticancer efficacy in combination with other anticancer drugs, such as cisplatin, 5-fluorouracil, and paclitaxel. However, the shortcomings of melatonin, such as its low bioavailability, rapid metabolism, and significant individual variation in secretion, have limited its clinical application in anticancer therapy. This limitation has been mitigated by targeted delivery and individualized therapy. Therefore, MLT may be a promising candidate for natural hormone therapy in the future.